Post-Traumatic Stress Disorder and its Somatic Comorbidities: A Review - Jakub Moder; Aleksandra Sadowska; Aleksandra Welkier; Adam Sobiński; Joanna Miśkiewicz; Aleksandra Dudek; Patrycja Pietrusińska; Patrycja Śliwa-Tytko; Anna Dziewierz; Paula Kwaśniewska (Journal of Education, Health and Sport)
As of today, research has shown that exposure to traumatic events and psychological trauma is a widespread phenomenon. Its association with PTSD and other various mental disorders has been widely studied. However, research suggests the exposure to such events is said to be correlated with early onset of specific diseases, increased healthcare utilization, and premature death. The aim of this review is to summarize the available literature and explore various diseases and their relations to PTSD. The areas of interest for this particular review will include cardiovascular, metabolic, and autoimmune diseases as well as inflammation. Ample evidence of the link between PTSD and somatic diseases (specifically cardiovascular, metabolic, and autoimmune disease as well as additional comorbidities that do not fit into either category) following it is presented, as well as some additional studies showing bidirectional relationships between PTSD and several illnesses. Several other notable comorbidities are discussed as well, followed by a brief overview of presented studies and their limitations as well as a conclusion. Last presented is a list of potential future research directions, followed by a generalized discussion of the review at hand. A strong recommendation for rigorous implementation of trauma-informed care in healthcare facilities is presented, along with research corroborating the need for such practice.